Violents jusqu’au meurtre ? Réflexions sur deux cas d’homicide - Rondeau, Roger (Criminologie, 1990)
When a youngster under eighteen is implicated in a homicide, the media vigorously denounce his violence and deny him integration in society. Roger Rondeau, a psychologist, has had occasion to meet youngsters who have committed this type of crime. He presents a dynamic analysis here of the personality of two of them in an effort to understand the meaning of their behaviour and the source of their aggression. His study shows, on the basis of the psychological aspect of the characters and events, that neither one of the two boys was a monster outside the social pale. The essential question is no doubt not to try to classify them as sick or guilty, as neurotics or delinquents; we should ask rather if they are not eloquent evidence of the failure of society.